Estrategias didácticas activas para la construcción de aprendizajes significativos, en la asignatura de Química. Periodo lectivo 2022- 2023. - Briceño Chalco, Jennifer Nayeli (2023)
Active didactic strategies allow to improve the teaching and learning process; since they offer opportunities that facilitate learning, make it possible to understand and apply it, strengthening thinking and communication skills. The objective of this work was <<To promote the construction of significant learning in students, through the application of active didactic strategies that encourage the active participation of students in the teaching and learning process of the subject of Chemistry in the First Year of Baccalaureate, of the “27 de Febrero” High school, academic period 2022-2023 >>. The method used was the inductive one. It started from direct observation, evidencing the lack of application of didactic strategies in the TLP of Chemistry, then, through the bibliographic search, the intervention proposal was elaborated and developed to address the problem. The approach is qualitative, the particularities of the classroom process are identified, explored and analyzed, such as: passivity, disinterest, little understanding and low grades of the students. According to the nature of the information, it is Participatory Action Research, through the intervention proposal, it was possible to motivate the collaboration and participation of students and researcher, to respond to the problem. It also corresponds to cross-sectional research, from the detection of the problem to the discussion of results occurs in a short period of time. The results obtained show that the active didactic strategies implemented and that were more effective in promoting the understanding of topics, interest and active participation of students, were: experimentation, gamification and simulation in virtual platforms, these promoted in them the construction of significant learning evidencing itself in the improvement of their academic performance. It is concluded that, through the application of active didactic strategies, accompanied by techniques, resources and pertinent didactic material, the TLP of subject of Chemistry was improved and the construction of significant learning in students was enhanced. Keywords: teaching strategies, chemistry teaching, constructivism, meaningful learning.